Effects Of Eight-week Pre Season Period Of High-intensity Interval Training And Small-sided Games On Repeated Sprint Ability And Wellness Status On Amateur Soccer Young Players - Rachad, Djeddi; Jebabli, Nidhal; Ben Abderrahman, Abderraouf (Journal of Sport Science Technology and Physical Activities, 2022)
This study was designed to analyze the effect of soccer players repeated-sprint ability (RSA) and evaluate the of pre-season perceived wellness between HIIT and SSG during 8-weeks of training , with two groups of 16 young footballers (GE-SSG;HIIT) performed 16 specific training sessions SSG [4vs4] and HIIT [30/30] ,were recorded before and after the training programmers: RSSA 40m x 6 test, and after each training session were assessed using the profile of Wellness status, sleep and sleep, fatigue, and muscle soreness ,These results indicate that HIIT Group (30/30s) Have achieved greater improvements than the SSG (4vs4) group on the Repeated sprint ability ,the results also led us to influence the HIIT group in terms of fatigue and muscle soreness at the expense of training with Small sided games , But coaches should be aware that both training methods are applicable methodologies for improving performance and physical level while monitoring the state of health and training-load in amateur soccer players' under-17.